2010
DOI: 10.1007/s13246-010-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence dosimetry for skin dose assessment during intraoperative radiotherapy for early breast cancer

Abstract: Dosimetry for intraoperative radiotherapy (IORT) after wide local excision for breast cancer using a 50 kV X-ray needle (Intrabeam) was performed in vivo using thermoluminescence dosimetry. Eight LiF:Mg,Ti chips were placed on the skin around the incision site after wide local excision while the tumour bed was irradiated to a prescribed dose of 5 Gy 10 mm from the applicator surface. The maximum and mean measured skin dose for 57 patients ranged from 0.64 to 7.1 Gy and 0.56 to 4.78 Gy, respectively, reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 9 publications
(9 reference statements)
4
26
0
Order By: Relevance
“…The univariate statistical analysis confirmed the dependencies of in vivo measured skin dose on distance from the measured point from the applicator shaft, in agreement with previous reports . The distance from the applicator shaft was an independent predictor of skin dose possibly because, for a fixed depth, an increase in distance implies a different geometry of irradiation, where the applicator is more oblique.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The univariate statistical analysis confirmed the dependencies of in vivo measured skin dose on distance from the measured point from the applicator shaft, in agreement with previous reports . The distance from the applicator shaft was an independent predictor of skin dose possibly because, for a fixed depth, an increase in distance implies a different geometry of irradiation, where the applicator is more oblique.…”
Section: Discussionsupporting
confidence: 90%
“…Monte Carlo simulation of a breast phantom with realistic tissue compositions and skin layers, demonstrated that in vivo dose depends on the size of applicator as well as the amount of breast tissue between the applicator and the skin. In the study of Fogg et al., the ratios between average doses measured with TLDs at 5 mm and at 15 mm from the point of insertion were 1.47, 1.22, 1.24, and 1.11 for the 3.5, 4.0, 4.5, and 5.0 cm applicators, respectively. This effect has been explained with more penetrating beam spectrum with larger applicators, but it should also be noted that the use of larger applicators is preferred on patients with larger breast size, as confirmed by correlation in our dataset among d min and applicator diameter (Spearman correlation test P ≪ 0.0001).As expected, in the univariate analysis, measured dose was also correlated with other variables related to the quantity of radiation emitted, such as the irradiation time and the prescribed dose which is specified, according to the TARGIT protocol, as the dose at 1 cm from the applicator surface in water.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The range of these results is comparable to previous studies which have reported 2.2 ± 1.0, 2.9 ± 1.5, and 2.9 ± 1.6 Gy for skin dose measurements taken 1-2 cm from the applicator using both EBT2 radiochromic film and TLDs. 4,5,14 RTQA2 film has been demonstrated in this work to produce in vivo dosimetry measurements that are consistent with EBT2 radiochromic film, TLDs, and OSLDs. The tumor cavity measurements for radiochromic film produced average differences between delivered and measured doses of 6.3%, −7.3%, −11%, and −16.6% for the 3, 3.5, 4, 4.5, and 5 cm applicators, with an average difference of −10.1% for all applicators.…”
Section: D In Vivo Measurementsmentioning
confidence: 52%
“…Energy and dose dependence (supralinearity) necessitate calibration in a similar beam quality and dose level, but this can potentially be performed using a superfi cial therapy X-ray unit instead of the INTRABEAM system (Eaton and Duck 2010 ). Common clinical uses of TLDs in radiotherapy include checking the dose in vivo to normal tissues such as the eyes, and they have been also been used with INTRABEAM to measure skin doses during breast intraoperative radiotherapy Fogg et al 2010 ).…”
Section: Tld Measurementmentioning
confidence: 99%